What are Government-Linked Companies (GLCs)? / Musliha Musman and Dr Salwa Muda - Musman, Musliha; Muda, Salwa (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Malaysian GLCs are deemed as hybrid organizations since the companies must achieve financial returns while fulfilling their social responsibilities (Mat Isa, C. M., Razak. M.T., Mustaffa. N.K., 2020; Norhayati & Siti-Nabiha, 2009). Previously, the GLCs were government organisations or public companies that had been privatised throughout the 1980s. This privatisation policy is based on two major objectives (Abdul Hamid, 2008). First, the policy would speedily achieve the New Economic Policy’s goal in providing more avenues for Bumiputera businesses to participate in the economic activities. Second, privatisation would reduce the government’s burden in providing essential services to the public. Despite the privatization, the government still holds a substantial ownership in these companies through Government-Linked companies (GLICs) (Mat Isa et. al, 2020; Norhayati & Siti-Nabiha, 2009; Abdul Hamid, 2008). Malaysian GLICs include Khazanah Nasional, Minister of Finances (MoF Inc), Kumpulan Wang Amanah Pencen (KWAP), and Bank Negara Malaysia (BNM), Permodalan Nasional Berhad (PNB), Employees Provident Fund (EPF) and Tabung Haji.